Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Pada Perusahaan Retail PT. Miniso International Company, Armada Town Square Magelang - Setiyawan, Akhmad Joko; Dewi, Desy Irana (Manajemen dan Bisnis, 2025)
This research aims to analyze the digital marketing strategies implemented by retail companies and their impact on increasing sales. The research method used is descriptive qualitative, with data collection through in-depth interviews, customer surveys, and document analysis. The results showed that PT Miniso has implemented various digital marketing strategies, including the use of social media, email marketing, and search engine optimization (SEO). These strategies proved effective in increasing brand visibility and attracting consumer interest, which contributed to a significant increase in sales. However, the study also identified several challenges faced, such as limited resources and the rapid changes in digital trends. Consumer perceptions of Miniso's digital marketing were largely positive, with many consumers feeling more connected and engaged with the brand through digital channels. From the results of the study, it was concluded that digital marketing plays a crucial role in increasing sales in retail companies.